Aut dedere aut judicare principle in international law - Кос’яненко, Сергій Олегович; Kosianenko, Serhii Olegovych (Одеса, 2024)
Дисертація присвячена дослідженню принципу aut dedere aut judicare в міжнародному праві. Принцип aut dedere aut judicare розглядається крізь призму трьох взаємопов’язаних аспектів: по-перше, захисту інтересів міжнародного співтовариства (недопущення безкарності за вчинені міжнародні злочини та забезпечення міжнародного порядку); по-друге, захисту інтересів держави (запитуючої та запитуваної) щодо екстрадиції, кримінального переслідування та кримінальної юрисдикції (зокрема, універсальної юрисдикції) та, по-третє, захисту прав та інтересів осіб, які підлягають кримінальному переслідуванню чи екстрадиції.

The thesis is devoted to a study of the aut dedere aut judicare principle in international law. The principle of aut dedere aut judicare is considered through the prism of three interrelated aspects: firstly, protection of the interests of the international community (preventing impunity for committed international crimes and ensuring international order); secondly, protection of the interests of a state (requesting and requested) regarding the extradition, criminal prosecutions and criminal jurisdiction (in particular, universal jurisdiction) and; thirdly, protection of the rights and interests of persons subject to prosecution or extradition. Based on the evolution of the doctrine and practice of international criminal law, a periodization of the development of the aut dedere aut judicare principle is presented: the period of the initial general contours of the principle of impunity, which were formulated in the works of such authors as F. Vitoria, G. Grotius and E. Vattel (16-18th centuries); the period of active development of extradition and origins of the customary obligation to apprehend or punish alleged perpetrators of certain crimes (18 - to the middle of the 20th century); the period after 1945 to 90s of the 20th century (the emergence of the international criminal tribunals ad hoc, the development of universal jurisdiction and inclusion of the aut dedere aut judicare clause in international multilateral and bilateral treaties on combating international crimes); the period from the 90s of the 20th century to the present (the work of the UN International Law Commission on the topic of the obligation to extradite or prosecute; the emergence of a permanent body of international criminal justice and other international and specialized courts and tribunals, which led to the emergence of a «third alternative» as a model of aut dedere aut judicare obligation). The author’s definition of the principle of aut dedere aut judicare is proposed, taking into account three possible alternatives and purposes of the principle: the aut dedere aut judicare principle establishes either the obligation to extradite the alleged offender or to transfer the case to the competent authorities of the requested state for prosecution or to surrender an alleged offender to a competent international (hybrid) criminal court or tribunal in order of ensuring international order, protection of the interests of a requesting and requested states and ensuring rights of persons involved in criminal proceedings. The activities of the International Law Commission on the topic «Obligation to Extradite or Prosecute (aut dedere aut judicare)» has been highlighted. The following main documents submitted by the International Law Commission has been analysed: Preliminary remarks «The Obligation to Extradite or Prosecute («aut dedere aut judicare») in International Law» (2004) by Special Rapporteur Z. Galicki; four reports of the Special Rapporteur Z. Galicki on the obligation to extradite or prosecute (aut dedere aut judicare) (the Preliminary report of 2006, the Second report of 2007, the Third report of 2008, the Fourth report of 2011); the Report of the Working Group on the Obligation to extradite or prosecute (aut dedere aut judicare) (2013); the Final report of the Working Group on the Obligation to extradite or prosecute (aut dedere aut judicare) (2014). A decade of study of the topic «Obligation to Extradite or Prosecute (aut dedere aut judicare)» of the ILC has not produced substantive results, such as draft articles on the obligation to extradite or prosecute. Special attention was given to the analysis of the numerous conventions aimed at combating international and transnational crimes which contained aut dedere aut judicare clause. Сonventions containing the aut dedere aut judicare clause can be divided into three main groups, depending on the relationship between the obligations to extradite and prosecute. The first group of the treaties includes provisions that impose an obligation to extradite, and criminal prosecution is an obligation only in case of refusal to extradite. Therefore, in this case, priority is given to extradition. The second group of conventions includes provisions that impose an obligation to prosecute, whenever the alleged offender is present in the territory of the State party, regardless of whether some other State party seeks extradition. The third group of treaties contains provisions which provide for an alternative for the state in whose territory the alleged offender is located. The state, because of the absolute freedom it has in the implementation of one of the two options, should be oriented at choosing the solution which is the most compatible with its national legal system. The analysis of the various sources of the obligation to extradite or prosecute is carried out with a view to determining the nature and scope of the obligation aut dedere aut judicare in international law. It was concluded that the obligation aut dedere aut judicare arises not only from the provisions of specific international treaties, but also from customary international norms. It has been shown that national criminal law constitutes an important source of the obligation to extradite or prosecute. The effective implementation of the principle of aut dedere aut judicare in each specific case will depend on the state’s fulfillment of both its international obligations and the implementation of the necessary measures (in particular, regarding the establishment of jurisdiction over criminal offenses and offenders) defined in national legislation concerning extradition and prosecution. It has been found that the fulfillment of the obligation to prosecute is conditioned by a number of actions: to conduct a preliminary inquiry, to submit the case to the relevant judicial authorities for prosecution, to fulfill the requirements regarding the timeliness of prosecution, to adopt the necessary legislation in order to criminalize certain types of conduct, to implement the relevant criminal jurisdiction, to co-operate and to exchange information with other states or international organizations. The requirements for the obligation to prosecute vary from treaty to treaty depending in particular on the type of international crime covered by the treaty. Fulfillment of the obligation to prosecute depends on the availability and compliance with national substantive and procedural norms regarding the conduct of criminal proceedings, in particular, the availability of sufficient evidence for the initiation of proceedings, provisions on amnesty or asylum, the need for the presence of the accused in the proceedings, provisions on the immunity of public officials from foreign criminal jurisdiction, etc. In the absence of sufficient evidence, the state is not obliged to prosecute the alleged offender. Three main constructions of the relationship between the two obligations (to extradite or prosecute) set forth in the principle of aut dedere aut judicare have been analyzed: the construction that favors extradition over prosecution; the construction that favors prosecution over extradition; an alternative approach. It has been shown that the content of the obligation to extradite or prosecute depends on the provisions of the treaties concluded between the parties and on the circumstances of each case. The decision to extradite or prosecute should be made by the state in accordance with its domestic laws and international legal obligations. It has been found that in the case of the appropriate treaty provisions, the principle of aut dedere aut judicare provides for the implementation of a third alternative (along with extradition and prosecution before the state’s own courts). The state in whose territory the alleged offender is located may be able to satisfy its obligations through the transfer of such person to an international criminal court or tribunal. Currently, such international conventions as: the 2006 International Convention for the Protection of All Persons from Enforced Disappearance, the 2007 African Charter on Democracy, Elections and Government, the Ljubljana-The Hague Convention on International Cooperation in the Investigation and Prosecution of the Crime of Genocide, Crimes against Humanity, War Crimes and other International Crimes, the last one was signed on February 2024 – enshrine a mechanism that allows states parties to choose between three options: prosecution, extradition or transfer to an international criminal court. The 1996 Draft code of crimes against the peace and security of mankind also enshrines the «triple» choice model proposed by the International Law Commission. The relationships between the aut dedere aut judicare principle and principle of universal jurisdiction have been brought to light. It has been found that the universal jurisdiction applies when there is no other connection to the state (territoriality, nationality or any other basis); aut dedere aut judicare obligation entails the transfer of the case to the competent authorities for prosecution or extradition, not the establishment of jurisdiction. Aut dedere aut judicare obligation is not limited to the situations in which a universal jurisdiction is required to be applied for the prosecution or extradition. It is emphasized that the recognition of the obligation to extradite or prosecute for jus cogens crimes as an erga omnes obligation is debatable. On the one hand, in international practice, one can find confirmation of the position that in case of committing international crimes that reach the level of jus cogens, the states are obligated to prosecute or extradite the perpetrators and such an obligation has acquired the character of erga omnes. On the other hand, the mere fact that a particular rule has acquired the status of jus cogens automatically does not mean that its related duty to extradite or prosecute has also gained that status. In practice, there are examples of granting amnesty or asylum to individuals who have committed jus cogens crimes.
Принцип aut dedere aut judicare у міжнародному праві
Keywords: obligation to extradite; obligation to prosecute; extradition; fight against impunity; international core crimes; transnational crimes; responsibility for international crimes; international criminal justice bodies; universal jurisdiction; international cooperation in the fight against crime; sources of international law; international community; human rights; international criminal law; зобов’язання видавати; зобов’язання здійснювати судове переслідування; екстрадиція; боротьба з безкарністю; основні міжнародні злочини; транснаціональні злочини; відповідальність за міжнародні злочини; органи міжнародної кримінальної юстиції; універсальна юрисдикція; міжнародна співпраця у боротьбі зі злочинністю; міжнародне співтовариство; права людини; міжнародне кримінальне право